Imunomodulator Ekstrak Etanol Daun Mimba (Azadirachta indica) terhadap Jumlah Sel Makrofag Peritoneal pada Mencit yang Diinduksi Vaksin BCG - Abror, Yogi Khoirul; Woelansari, Evy Diah; Suhariyadi, Suhariyadi (Jurnal Teknologi Laboratorium, 2018)
This research was conducted to determine the immunomodulatory effect of ethanol extract of neem leaves (Azadirachta indica) to the number of peritoneal macrophages in mice wich induced by BCG vaccine. Bacillus Calmette-Guerin (BCG) vaccine contained an attenuated Mycobacterium bovis. Mycobacterium bovis belongs to the Mycobacterium Tuberculosis Complex (MTC) group that has a similar phenotype characteristic with Mycobacterium tuberculosis and similar clinical manifestations of tuberculosis.The type of the research that used in this study is laboratory experimental research with Post Test Design Design Only Control Group Design. The research was conducted at the Faculty of Veterinary Medicine of Airlangga University in July 2017 using 25 male mice divided into five groups. The dosage of ethanol extract of the neem leaves given was 200 mg / Kg BW with variation for two days, four days, and six days are given.In the result of statistical data analysis using Kruskal-walis test, it is known that the significance value p = 0,03 (p <0,05), that means immunomodulatory of ethanol extract of neem leaves (Azadirachta indica) give an effect to peritoneal macrophage cell number in mice wich induced by BCG vaccine, so that neem leaves ethanol extract can be applied to tuberculosis patients.